2017
DOI: 10.1167/iovs.17-21818
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Macular, Skin, and Serum Carotenoids

Abstract: PurposeOcular and systemic measurement and imaging of the macular carotenoids lutein and zeaxanthin have been employed extensively as potential biomarkers of AMD risk. In this study, we systematically compare dual wavelength retinal autofluorescence imaging (AFI) of macular pigment with skin resonance Raman spectroscopy (RRS) and serum carotenoid levels in a clinic-based population.MethodsEighty-eight patients were recruited from retina and general ophthalmology practices from a tertiary referral center and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 61 publications
(77 reference statements)
5
45
6
Order By: Relevance
“…Groups have argued that visual axis opacities such as cataracts may alter measurements; however, we did not find a significant 'cataract effect' on volume measurements [71,76]. The technique is also highly reproducible even in the face of significant ocular pathology such as exudative AMD and diabetic macular edema [71]. Unfortunately, dual wavelength autofluorescence is not perfect either, as it requires pupillary dilation and expensive equipment to obtain the measurements.…”
Section: Modalities To Clinically Measure Mpmentioning
confidence: 60%
See 4 more Smart Citations
“…Groups have argued that visual axis opacities such as cataracts may alter measurements; however, we did not find a significant 'cataract effect' on volume measurements [71,76]. The technique is also highly reproducible even in the face of significant ocular pathology such as exudative AMD and diabetic macular edema [71]. Unfortunately, dual wavelength autofluorescence is not perfect either, as it requires pupillary dilation and expensive equipment to obtain the measurements.…”
Section: Modalities To Clinically Measure Mpmentioning
confidence: 60%
“…7), we have found that volumetric measurements appear to be superior to previously used optical densities in regards to their correlative power with other carotenoid measurement techniques [71]. Groups have argued that visual axis opacities such as cataracts may alter measurements; however, we did not find a significant 'cataract effect' on volume measurements [71,76]. The technique is also highly reproducible even in the face of significant ocular pathology such as exudative AMD and diabetic macular edema [71].…”
Section: Modalities To Clinically Measure Mpmentioning
confidence: 73%
See 3 more Smart Citations